DENOTATIVE AND CONNOTATIVE MEANING IN LYRIC “MOCKINGBIRD” SONG BY EMINEM - Indah Lestari; Dwi Nitisari (Jurnal Sosial Humaniora dan Pendidikan, 2022)
This research aims at analyzing several words, phrases, and clauses in 'Mockingbird' song sung by Eminem (2004) which have denotative and connotative meaning and finding the relation between the meaning found to the context of the singer's real life. In analyzing the denotative and connotative meaning of the selected words, phrases, and clauses, this study uses Palmer’s theory of denotative and connotative (1976) as a theoretical basis. The source of data was from “Mockingbird” song lyric by Eminem. This study uses descriptive qualitative as the design of study. After analyzing the data from the lyrics, this study found that (1) some lyrics contained with connotative and denotative meaning on referring a specific object or emotion. (2) Connotative meaning of these lyric have a relation with context family relationship in Eminem's real life .